(untitled) (Research, Society and Development, 2022)
The urban growth of Brazilian cities occurred in a disorganized way, without urban and environmental planning, causing several problems for the population. Several cities were initially occupied near the rivers and did not take into account their natural dynamics, causing disastrous floods and inundations due to rainfall rates that provide an increase in the volume of water bodies. In the city of Crato it was no different, in that, currently, the areas of water runoff in the rainy season are impermeable causing serious problems for the population, such as heavy flooding, processes, which deprive the population of transit with their vehicles and even the impossibility of traffic for residents and access to their homes. Thus, this paper aims to define parameters related to the spatial-temporal distribution of precipitation and flow data for the micro-basin of the Granjeiro river. Thus, the watershed area of the Granjeiro river and its watercourses were delimited, as well as applications of statistical models in rainfall data of the region and an estimate of the intensities and maximum flows by the rational method, for certain return periods. It was verified that most of the maximum annual precipitation is around 75 to 100 mm, and that the distribution of rainfall in the region is not necessarily uniform and easily predictable.